(untitled) (Shaheed Smriti Journal, 2024)
This study aims to explore students’ attitudes toward entrepreneurship education in Chitwan District, Nepal, focusing on their practical, cognitive, and affective perspectives. Using a quantitative research design, data were collected from a sample of 200 students enrolled in entrepreneurship programs across several colleges. A structured questionnaire was administered to assess students’ attitudes regarding entrepreneurship education, including their enthusiasm, knowledge, and emotional connection to self-employment. Data were analyzed using descriptive statistics to identify patterns and trends. The findings reveal that while students show a strong interest in entrepreneurship, with high motivation to pursue self-employment, they feel underprepared for practical application. Despite a solid understanding of business planning and financing, students report low levels of support for applying their knowledge in real-world contexts. The study concludes that while entrepreneurship education is positively received, more hands-on experiences, such as guest speaker interactions and practical business activities, are essential to bridge the gap between theory and practice.